2018
DOI: 10.1038/emm.2017.272
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin modulates the alleviation of atopic dermatitis caused by the marine-derived compound dihydroaustrasulfone alcohol

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease, and its prevalence is increasing. AD usually elicits skin barrier dysfunction, dry skin and itching. As the mechanisms of AD remain unknown, there is an urgent need to find effective therapies. Because of the diversity and complexity of marine environments, the discovery of drugs from marine organisms as novel therapeutic agents for human diseases has seen renewed interest. Dihydroaustrasulfone alcohol (WA-25), the synthetic precursor of austrasulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…It was previously indicated that induction of HO-1 plays a protective role in several inflammation-related diseases (7), including AD, and HO-1 has been reported to exhibit therapeutic efficiency in AD (8)(9)(10)(11). Chen and Zhong (16) revealed that HO-1 combined with microRNAs may affect certain skin diseases, such as ischemia, hypoxia, rheumatoid arthritis and AD, by regulating the functions of T cells, dendritic cells and mast cells, and the release of chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was previously indicated that induction of HO-1 plays a protective role in several inflammation-related diseases (7), including AD, and HO-1 has been reported to exhibit therapeutic efficiency in AD (8)(9)(10)(11). Chen and Zhong (16) revealed that HO-1 combined with microRNAs may affect certain skin diseases, such as ischemia, hypoxia, rheumatoid arthritis and AD, by regulating the functions of T cells, dendritic cells and mast cells, and the release of chemokines and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Kim et al ( 18 ) reported that 2,3-dimethoxy-2'-hydroxychalcone, a derivative of 2'-hydroxychalcone in the flavonoid family, can alleviate skin inflammation by inhibiting TNF-α-induced intercellular adhesion molecule-1 expression and adhesion of monocytes to keratinocytes, by suppressing NF-κB activation and inducing HO-1 expression in keratinocytes. Hung et al ( 10 ) demonstrated that WA-25 can protect against AD by increasing the expression levels of HO-1 and Nrf2. Gene therapy of AD via targeting the HO-1 gene has been reported in several studies; however, AD therapy using the HO-1 protein is limited by its inability to enter cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-inflammatory activity method used was modified from our previous studies [16,17,18]. We examined the effects of steroids 1 – 5 on pro-inflammatory iNOS and COX-2 protein expressions in LPS-stimulated RAW264.7 cells by Western blotting analysis.…”
Section: Methodsmentioning
confidence: 99%